Dexamethasone inhibits human interleukin 2 but not interleukin 2 receptor gene expression in vitro at the level of nuclear transcription. - Boumpas, D T (1991)
Glucocorticosteroids have an inhibitory effect on the expression of interleukin 2 (IL-2) and interleukin 2 receptor (IL-2R) genes. To determine the mechanisms of this inhibition, human T lymphocytes were stimulated with mitogens in the presence of dexamethasone. Nuclear transcription run-off assays showed that high doses of dexamethasone inhibited the transcription of the IL-2 gene but not that of the IL-2R gene. Post-transcriptionally, high doses of dexamethasone (10(-4) M) were required to inhibit IL-2R mRNA levels by 50%, whereas lower doses (10(-6) M) inhibited by greater than 70% the accumulation of IL-2 mRNA. IL-2 mRNA half-life decreased in the presence of dexamethasone (10(-6) M) by approximately 50%. At the protein product level, dexamethasone inhibited both IL-2 production, as well as cell surface and soluble forms of IL-2R. IL-2R gene expression was inhibited for at least 72 h after exposure of cells to dexamethasone. In the presence of exogenous IL-2, dexamethasone failed to exert a significant effect on the production of IL-2R protein. These data indicate that dexamethasone has a greater effect on the expression of the IL-2 gene than on the IL-2R gene. Dexamethasone both inhibits transcription of the IL-2 gene and decreases the stability of IL-2 mRNA. The effect of dexamethasone on the IL-2R gene is post-transcriptional and may result indirectly from decreased IL-2 production.